2021
DOI: 10.3390/ma14247845
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Stress Distributions in 3D Printed Graded Plates with a Circular Hole

Abstract: An experimental investigation is presented for the stress distributions in functionally graded plates containing a circular hole. On the basis of the authors’ previously constructed theoretical model, two kinds of graded plates made of discrete rings with increasing or decreasing Young’s modulus were designed and fabricated in virtue of multi-material 3D printing. The printed graded plates had accurate size, smooth surface, and good interface. The strains of two graded plates under uniaxial tension were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Yang et al (2020) extended the idea of FGM layer to reduce the SCF in the plate under out-of-plane bending load condition. Yang et al (2021) experimentally investigated the stress concentration reduction for a circular hole with FGM layer and observed that the experimental results have good agreement with theoretical results. Goyat et al (2021) analyzed the SCF reduction and optimized the parameters of level set based FGM for inclined pair of circular holes.…”
Section: Introductionmentioning
confidence: 59%
“…Yang et al (2020) extended the idea of FGM layer to reduce the SCF in the plate under out-of-plane bending load condition. Yang et al (2021) experimentally investigated the stress concentration reduction for a circular hole with FGM layer and observed that the experimental results have good agreement with theoretical results. Goyat et al (2021) analyzed the SCF reduction and optimized the parameters of level set based FGM for inclined pair of circular holes.…”
Section: Introductionmentioning
confidence: 59%
“…Njemački inženjer Ernst Gustav Kirsch je 1898. godine prvi dao analitičko rješenje ovog problema [2] (Kirschov problem), a njegovo se rješenje temelji na klasičnoj teoriji elastičnosti gdje je vrijednost koncentracije naprezanja uvijek jednak trojci, i to neovisno o promjeru otvora i o materijalnim parametrima ploče. U zadnjih sto godina provedena su mnoga eksperimentalna istraživanja na pločama od različitih materijala [3], s različitim brojem i oblicima izbušenih otvora [4], a pregledom dosadašnje literature [5], [6] je uočeno da su vrijednosti koncentracije naprezanja uvijek manje od teorijskih pretpostavki. Poznavanje točne vrijednosti koncentracije naprezanja je vrlo bitno u inženjerstvu jer su upravo na tim mjestima moguće pojave prvih pukotina.…”
Section: Uvodunclassified
“…Goyat et al (2022) proposed level set function-based graded FGM for SCF reduction near hole in a finite plate. Yang et al (2021) experimentally investigated the effect of FGM parameters on SCF around hole on the universal testing machine. They observed a good agreement between the result obtained from mathematical modeling and experimental investigation.…”
Section: Introductionmentioning
confidence: 99%